2016
DOI: 10.1021/acs.analchem.6b01627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multidentate Metal Interactions on the Structure of Collisionally Activated Proteins: Insights from Ion Mobility Spectrometry and Molecular Dynamics Simulations

Abstract: Much remains to be learned about the way in which bound metal ions modulate the response of electrosprayed proteins and protein complexes to collisional excitation. Nonspecific metal adducts can affect the extent of collision-induced unfolding (CIU) and collision-induced dissociation (CID). Here, we examine how Na(+) and Ca(2+) adducts alter the CIU response of monomeric proteins under native electrospray conditions. Both of these metals are commonly encountered in biological samples. Measured collision cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 84 publications
6
26
0
Order By: Relevance
“… 54 To test this hypothesis, we used collisional activation in the source region of the mass spectrometer to disrupt noncovalent bonds within the peptide anions prior to niECD. Previous studies have shown that vibrational activation of gaseous peptide and protein ions by collisions or absorption of infrared photons can result in partial or full unfolding, 52 , 62 , 83 and that the stability of intramolecular interactions generally follows the order salt bridges > ionic hydrogen bonds > neutral hydrogen bonds > hydrophobic bonds. 44 , 45 , 53 , 55 , 84 Instead of the 10 V skimmer potential in the experiments for Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 54 To test this hypothesis, we used collisional activation in the source region of the mass spectrometer to disrupt noncovalent bonds within the peptide anions prior to niECD. Previous studies have shown that vibrational activation of gaseous peptide and protein ions by collisions or absorption of infrared photons can result in partial or full unfolding, 52 , 62 , 83 and that the stability of intramolecular interactions generally follows the order salt bridges > ionic hydrogen bonds > neutral hydrogen bonds > hydrophobic bonds. 44 , 45 , 53 , 55 , 84 Instead of the 10 V skimmer potential in the experiments for Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 5 , 9 The tight association can be rationalized by multivalent charge interactions between serum albumin and ligand. 29 In fact, this protein contains a protected phospholipid-binding pocket, in addition to several low-affinity sites, in which the lipid is bound via contacts between basic residues and the ionic phosphate headgroup. 30 Our data suggest that lipid interactions with selected binding sites on soluble proteins can mirror effects observed for membrane proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The high concentration of ammonium acetate (20 mM, pH 7.4) added for native MS caused the ammonium adduction of K18. [36][37] The ESI-MS spectra of K18 with ATP (K18:ATP = 1:1 and 1:10) indicated that the number of ATP molecules bound to a K18 ion increased with increase in the ATP concentration ( Figure 3a). The property of K18-ATP binding was investigated from the relative abundance of K18 and K18-ATP complex peaks in the mass spectrum of K18:ATP = 1:10 ( Figure 3b).…”
Section: Nonspecific Electrostatic Interactions Between K18 and Atpmentioning
confidence: 99%